2022
DOI: 10.3390/ijerph192315919
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and Barriers of Artificial Intelligence Applications in Rehabilitation: A Mixed-Method Approach

Abstract: Artificial intelligence (AI) has been used in physical therapy diagnosis and management for various impairments. Physical therapists (PTs) need to be able to utilize the latest innovative treatment techniques to improve the quality of care. The study aimed to describe PTs’ views on AI and investigate multiple factors as indicators of AI knowledge, attitude, and adoption among PTs. Moreover, the study aimed to identify the barriers to using AI in rehabilitation. Two hundred and thirty-six PTs participated volun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Using artificial intelligence-based communication for support has not been studied much in the context of rehabilitation, and there is no clear evidence regarding the current understanding of patients’ views and preparedness to use artificial intelligence in their practices. 40 A positive finding in this study is the support and guidance provided by healthcare professionals to patients. Although physiotherapists and nurses play a significant role and accompany patients during rehabilitation, this aspect was not clearly described in the studies.…”
Section: Discussionmentioning
confidence: 68%
“…Using artificial intelligence-based communication for support has not been studied much in the context of rehabilitation, and there is no clear evidence regarding the current understanding of patients’ views and preparedness to use artificial intelligence in their practices. 40 A positive finding in this study is the support and guidance provided by healthcare professionals to patients. Although physiotherapists and nurses play a significant role and accompany patients during rehabilitation, this aspect was not clearly described in the studies.…”
Section: Discussionmentioning
confidence: 68%
“…However, it has been pointed out that even here the ability of the interventionist who is experienced with AI may be prove to be a highly salient and influential factor. 21 Another application of AI for dementia that may impact health positively reveals robotic pets to have a beneficial impact on alleviating stress and anxiety in this group, 22 but this should be examined further, as the use of any robotic device for securing the comfort and support of an older or impaired adult may engender-rather than mitigate-stress.…”
Section: Resultsmentioning
confidence: 99%
“…In earlier study, the majority of the participants indicated that in addition to the expense of equipment and therapy, there are also implementation costs, such as those associated with software development, as well as providing AI education and training programs, which might all be expensive and limit the adoption of AI. ( Alsobhi et al, 2022 ) Lack of software and high equipment cost were also identified as barriers to AI implementation in the healthcare utility in another study. ( Goyal and Khatib, 2022 ) Such hurdles may necessitate substantial financial support by the healthcare authorities to ensure the availability of AI technology in the community pharmacy setting.…”
Section: Discussionmentioning
confidence: 99%